The Influence of Social Environmental Knowledge, Ecoliteracy, and Green Lifestyle on Senior High School Students’ Environmental Concern Character - Moh. Balya Ali Sya’ban; Alwin Alwin; Agung Adiputra; Mushoddik Mushoddik (JAMBURA GEO EDUCATION JOURNAL, 2025)
This study aims to examine the influence of social environmental knowledge, ecoliteracy, and green lifestyle on students' environmental concern character within the school setting. Research on students’ environmental concern character is very important to conduct because, despite the implementation of various environmental education programs in schools, many students still exhibit a lack of concern for the environment, raising questions about the effectiveness of the influencing factors. Furthermore, debates continue regarding the effectiveness of social environmental knowledge, ecoliteracy, and green lifestyle, which have not yet fully shaped students’ environmental concern character. Therefore, this study seeks to examine whether social environmental knowledge, ecoliteracy, and green lifestyle influence students’ environmental concern character within the school setting. This study employed a survey method, in which the data were collected using a closed-ended questionnaire with a five-point Likert scale for the environmental concern character variable and the green lifestyle variable. The variable of social environmental knowledge level was measured using a multiple-choice test, whereas the ecoliteracy variable was measured using an observation-based questionnaire. The data analysis technique employed was path analysis. All variable data, including the levels of social environmental knowledge, ecoliteracy, and green lifestyle, were entered into a correlation matrix to determine the degree of relationships among the variables. The respondents were 60 randomly selected students from SMA Muhammadiyah 23 Jakarta, who served as the unit of analysis. The findings indicate that students’ environmental concern character is directly influenced by the level of social environmental knowledge, ecoliteracy, and green lifestyle. In addition, this study found that social environmental knowledge and ecoliteracy indirectly influence environmental concern character through green lifestyle. Similarly, ecoliteracy was also found to indirectly influence environmental concern through green lifestyle. Based on these findings, it can be concluded that variations in students' environmental concern character are influenced by variations in their levels of social environmental knowledge, ecoliteracy, and green lifestyle. Therefore, these three factors significantly contribute to shaping students’ character to be more environmentally conscious in their school environment.